Características vocais de crianças relacionadas com idade e indicadores antropométricos - Finger, Leila Susana (2015)
The development of children s vocal apparatus reflects in their voice characteristics. Objectives: To review the characteristics of the child s voice; to assess and correlate the results of the acoustic analysis of the glottal source, maximum phonation times (MPT), body height and body mass index (BMI) of children aged 4-8 years. Methods: A sample of 484 eutrophic children without a speech-language pathology diagnosis of dysphonia; mailing of questionnaires to parents; auditory screening; BMI determination, and auditory-perceptual analysis of voice (CAPE-V scale); acoustic assessment of /a:/ using the Multi Dimensional Voice Program Advanced; /a,i,u/ MPT measurements; descriptive statistics analysis, t-test and multiple regression (SPSS, significance at 5%). Results: hoarseness and/or breathiness is expected, as well as voice instability; increased loudness, and hard glottal attack; lowered fundamental frequency (f0) as the child grows; measures of jitter, shimmer, noise-to-harmonics ratio (NHR), and voice turbulence index (VTI) tend to be higher in younger children and decrease with body growth and increasing age; due to the maturation of the structures, increased soft phonation index (SPI) is also expected; MPT in seconds parallels the child s age in years, with slightly more sustained phonation than the respective chronological age. In childhood, voice disorders are frequent and more prevalent in boys, with characteristics such as hoarseness and breathiness; lowered f0 and increased jitter and shimmer in dysphonic voices. Original papers: lower f0 as age increases; lower f0 values in girls; greater jitter, shimmer, and VTI measures in girls at six years; higher SPI in boys at seven years; negative correlations between f0, height, and BMI at four years; positive correlations between height and BMI and measures of jitter, shimmer, and VTI, as well as between height and NHR in girls at five years; variability in amplitude and height at seven years in girls; SPI and height in boys at five and seven years. Mean /a/ MPTs for boys at four, five, six and seven years, respectively: 3.77s, 5s, 5.85s, and 7.5s. Mean /a/ MPTs for girls at the same ages: 3.89s, 4.89s, 5.61s, and 6.61s, respectively. Mean /i/ MPTs for boys: 3.49s, 4.96s, 5.72s, and 6.88s. Mean /i/ MPTs for girls: 3.49s, 4.73s, 5.41s, and 6.63s. Mean /u/ MPTs for boys: 3.64s, 4.85s, 5.76s, and 7.08s. Mean /u/ MPTs for girls: 3.54s, 4.73s, 5.64s, and 6.47s. Longer /a/ MPT in boys at seven years, which correlated positively with height. Conclusion: Body height seemed to be the anthropometric measure with the greatest correlation to the acoustic measures, predominantly in girls. The age ranges showing acoustic abnormalities coincided with those rated as having mild deviance in auditory-perceptual analysis. Children s MPT increases with age; /a,i,u/ MPTs in seconds follow the age in years; at seven years, /a/ MPT was longer for boys and influenced by body height, while BMI had no influence on MPT.